PENGGUNAAN DATABASE INLISLITE DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN ACEH TAMIANG - Atikah Adani; Retno Sayekti; Rina Devianty (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the use of the INLISLite application in library management at the Library and Archives Office of Aceh Tamiang Regency. INLISLite is library automation software developed by the National Library of the Republic of Indonesia (Perpusnas) to support the transformation of libraries towards digitalization. Although the Library and Archives Office of Aceh Tamiang Regency has implemented INLISLite, observations reveal that many library users have not yet optimally utilized this system. Instead, they often search for information manually or directly ask librarians, leading to inefficient search times and negatively impacting library performance. Additionally, this study identifies challenges in the implementation of INLISLite, such as limited computer facilities and the lack of backup power, which hinder system operations during power outages. This research provides insights into the strategies used by the library to optimize the use of INLISLite and identifies the challenges faced in the implementation of library automation systems at the regional level.